Pandemic Trade : Covid-19, Remote Work and Global Value Chains - Espitia, Alvaro; Mattoo, Aaditya; Rocha, Nadia; Ruta, Michele; Winkler, Deborah (World Bank, Washington, DC, 2021)
This paper studies the trade effects of Covid-19 using monthly disaggregated trade data for 28 countries and multiple trading partners from the beginning of the pandemic to June 2020. Regression results based on a sector-level gravity model show that the negative trade effects induced by Covid-19 shocks varied widely across sectors. Sectors more amenable to remote work contracted less throughout the pandemic. Importantly, participation in global value chains increased traders’ vulnerability to shocks suffered by trading partners, but it also reduced their vulnerability to domestic shocks.